High-thermal-conductivity flame-retardant PBO nano-composite film and preparation method thereof
Through the composite of MXene nanosheets modified with natural polyphenol compounds with PBO nanofibers, the problem of poor compatibility between thermal fillers and polymer matrix is solved, and PBO nanocomposite films with high thermal conductivity, excellent mechanical properties and flame retardant properties are achieved, which are suitable for high power density electronic devices and heat dissipation needs of aerospace.
Patent Information
- Application Number
- CN202510850541.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-24
- Publication Date
- 2025-08-12
AI Technical Summary
Among the existing polymer-based thermally conductive materials, the thermally conductive filler has poor compatibility with the polymer matrix, resulting in high interface thermal resistance and serious mechanical performance losses, making it difficult to meet the heat dissipation needs of high-power electronic devices.
MXene nanosheets modified with natural polyphenol compounds are compounded with PBO nanofibers, and strong interface effect is formed through π-π action and hydrogen bond cross-linking. Combined with the sol-gel-film conversion process, the MXene uniform dispersion in the PBO fiber network is achieved, forming a fine "brick-mud" shell-like pearl layer structure.
The thermal conductivity, mechanical properties and flame retardant properties of thermal composite materials are improved, and the heat dissipation requirements in high-power density electronic devices and aerospace fields are met. The thermal conductivity is greater than 37 W·m-1K-1, the tensile strength is greater than 240 MPa, and the limit oxygen index is greater than 54%.
Smart Images

Figure CN120463991A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of thermal conductive composite materials, and in particular relates to a high thermal conductive flame retardant PBO nanocomposite film and a preparation method thereof. Background Art
[0002] With the rapid development of high-tech technologies such as artificial intelligence, 5G communications, the Internet of Things, and big data, components in the electronics industry are gradually developing towards high power, high integration, and high density. The heat generated by electronic devices during high-load operation is increasingly difficult to dissipate effectively, which inevitably leads to local heat accumulation problems, thereby affecting the operating efficiency, service life, and reliability of the equipment and its components. It can be seen that the development of thermal management materials with efficient heat dissipation is imperative. Although traditional thermal management materials such as metals and ceramics have high thermal conductivity, their defects such as high density and poor brittleness are not conducive to the increasing miniaturization and integration of electronic products. Polymer-based thermal conductive composite materials have gradually stood out in the interface and packaging materials for thermal management of electronic components due to their advantages such as light weight, flexibility, corrosion resistance, and easy molding and processing. However, the polymer matrix usually has low thermal conductivity (the thermal conductivity is usually less than 0.5 W m -1 K -1 ), poor temperature resistance and flammability. By adding inorganic thermal conductive fillers (such as graphene, carbon nanotubes and boron nitride) to polymers, high thermal conductivity (>15 W m -1 K -1 However, current polymer-based thermal conductive materials still suffer from common problems such as difficulty in uniformly dispersing inorganic thermal conductive fillers, severe loss of mechanical properties, and a significant increase in density.
[0003] Poly(p-phenylene benzobisoxazole) (PBO) fibers have the "four super" properties of ultra-high strength, ultra-high modulus, ultra-high heat resistance and ultra-flame retardancy. At the same time, their highly oriented and crystalline structure show good axial thermal conductivity, but as a low-dimensional material, they are difficult to be used directly for thermal management. In recent years, PBO nanofibers derived from PBO fibers have been regarded as having broad application prospects in the fields of electronic information and 5G communications. However, the interaction between PBO nanofibers is poor, resulting in less than ideal thermal conductivity. The new two-dimensional material MXene nanosheet has a theoretical thermal conductivity of up to 108 Wm due to its special structure and rich surface functional groups. -1 K −1, showing broad application prospects in thermal management, but the mechanical properties of pure MXene films are poor and difficult to meet application requirements. The composite of PBO nanofibers and MXene is expected to obtain high-performance polymer-based thermal conductive materials. Patent CN119823426 A discloses a MXene-edge graphene oxide heterojunction / PBO fiber multifunctional thermal conductive composite film and its preparation method, but due to the limitations of the dispersibility and compatibility of the matrix and filler, the thermal conductivity and mechanical strength of the prepared composite film are still relatively low. Therefore, how to improve the interfacial force between the thermally conductive filler and the polymer matrix to further improve the thermal conductivity and mechanical properties of the composite material is a problem that those skilled in the art urgently need to solve. Summary of the Invention
[0004] In order to solve the problems in the prior art of poor compatibility between polymer matrix and thermal conductive filler, weak interaction force and unsatisfactory thermal conductivity and mechanical properties of composite materials, the present invention provides a high thermal conductivity and flame retardant PBO nanocomposite film and its preparation method.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is: One of the purposes of the present invention is to provide a method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film, which comprises the following steps: (1) Preparation of PBO nanofiber dispersion: PBO fibers were added to mixed acid and stirred to obtain PBO nanofiber dispersion; (2) Preparation of MXene nanosheets modified with natural polyphenol compounds: natural polyphenol compounds and MXene nanosheets are ultrasonically dispersed in deionized water, and then a pH regulator is added to the dispersion until the system becomes weakly alkaline. After stirring, the mixture is freeze-dried to obtain MXene nanosheets modified with natural polyphenol compounds; (3) Preparation of PBO / MXene nanocomposite film: MXene nanosheets modified with natural polyphenol compounds are added to the PBO nanofiber dispersion, stirred evenly, and then a mixed acid aqueous solution is added dropwise to obtain a PBO / MXene nanocomposite acid sol; the sol is allowed to stand to obtain an acid gel, and then a solvent exchange is performed to obtain a PBO / MXene nanocomposite hydrogel; the sol is then calendered and dried to obtain a PBO / MXene nanocomposite film.
[0006] Preferably, the mixed acid in step (1) is prepared by mixing methanesulfonic acid (MSA) and trifluoroacetic acid (TFA) in a mass ratio of 1:(1.0-1.5).
[0007] Preferably, the mass ratio of the PBO fiber to the mixed acid used in step (1) is 1:(200-400).
[0008] Preferably, the stirring temperature in step (1) is 25°C to 40°C, and the stirring time is 2 to 3 days.
[0009] Preferably, the natural polyphenol compound in step (2) is selected from any one of tannic acid, ellagic acid, epigallocatechin gallate, chlorogenic acid, catechin, and quercetin.
[0010] Preferably, the mass ratio of the natural polyphenol compound and the MXene nanosheets used in step (2) is (1-5):1.
[0011] Preferably, the concentration of MXene nanosheets in the dispersion obtained in step (2) is 4-8 mg / mL.
[0012] Preferably, the pH regulator in step (2) is selected from any one of ammonia water, sodium hydroxide, sodium carbonate, sodium bicarbonate, and tris(hydroxymethyl)aminomethane, and is used to adjust the pH of the system to 8-9.
[0013] Preferably, the stirring temperature in step (2) is 25°C to 30°C, and the stirring time is 12 to 24 hours.
[0014] Preferably, the vacuum degree of the freeze-drying in step (2) is 6.0~10.0Pa, the temperature is -50℃~-99℃, and the time is 24h~72h.
[0015] Preferably, the mass ratio of the natural polyphenol compound modified nanosheets used in step (3) to the PBO fibers in the PBO nanofiber dispersion is 1:(1-4).
[0016] Preferably, the stirring time in step (3) is 15 to 20 minutes.
[0017] Preferably, the mixed acid aqueous solution in step (3) is prepared by mixing methanesulfonic acid, ethyl acetate and water in a mass ratio of 400:(115-130):(15-25).
[0018] Preferably, the mass ratio of the mixed acid aqueous solution in step (3) to the PBO fibers in the PBO nanofiber dispersion is (285-315):1.
[0019] Preferably, the standing time in step (3) is 24 hours.
[0020] Preferably, the solvent exchange in step (3) is performed by first soaking in an aqueous solution of methanesulfonic acid and then soaking in water to completely remove the acid.
[0021] More preferably, the mass ratio of methanesulfonic acid to water in the methanesulfonic acid aqueous solution is (0-4):1.
[0022] Specifically, it is soaked in methanesulfonic acid / water (160 g / 40 g), methanesulfonic acid / water (140 g / 60 g), and then soaked in water.
[0023] More preferably, the soaking time in the methanesulfonic acid aqueous solution is 12 hours; the number of soaking in water is 6 to 13 times, each soaking time is 1 to 2 hours.
[0024] Preferably, the pressure of the calendering molding in step (3) is 0.6~1.0kPa.
[0025] Preferably, the drying temperature in step (3) is 30°C to 50°C, and the drying time is 24 to 48 hours.
[0026] The second purpose of the present invention is to protect the high thermal conductivity and flame retardant PBO nanocomposite film prepared by the method.
[0027] Preferably, the thermal conductivity of the obtained high thermal conductivity flame retardant PBO nanocomposite film is greater than 37 W·m -1 K -1 , tensile strength greater than 240 MPa, and limiting oxygen index greater than 54%.
[0028] Compared with the prior art, the present invention has the following significant advantages: (1) The present invention utilizes the hydrogen bond assembly effect between the polyphenol structure of natural polyphenol compounds and the surface functional groups (-F, -Cl, -OH) of MXene to form a stable natural polyphenol compound-modified MXene nanoelement. Then, through the strong π-π interaction and hydrogen bond crosslinking between the polyphenol compound and the PBO nanofiber matrix, it has the dual effects of enhancing the interface effect and improving the dispersibility. At the same time, it provides an additional thermal bridge, effectively reducing the interfacial thermal resistance between MXene and PBO nanofibers, and solving the problems of uneven dispersion of thermal conductive fillers and high interfacial thermal resistance in existing thermal conductive composite materials.
[0029] (2) The present invention adopts a sol-gel-membrane conversion process to uniformly disperse the functionalized MXene in the PBO nanofiber network structure, forming a fine "brick-mud" shell nacre-like oriented structure to achieve enhanced mechanical properties.
[0030] (3) The PBO / MXene nanocomposite film provided by the present invention can simultaneously have excellent thermal conductivity, mechanical properties, flame retardancy, and thermal stability when a low amount of MXene is added, and can meet the heat dissipation requirements of high-power density electronic devices, electrical equipment, aerospace and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 PBO / 40wt%TA-Ti3C2T prepared in Example 1 xOptical photograph of nanocomposite film.
[0032] Figure 2 PBO / 40wt%TA-Ti3C2T prepared in Example 1 x Cross-sectional morphology of the nanocomposite film.
[0033] Figure 3 This is a comparison of infrared thermal imaging of using the PBO nanocomposite films prepared in Example 1 and Comparative Examples 1-2 as heat dissipation substrates for ceramic heaters.
[0034] Figure 4 PBO / 40wt%TA-Ti3C2T prepared in Example 1 x Microscopic morphology of the tensile fracture surface of the nanocomposite film.
[0035] Figure 5 These are stress-strain curves and strength-modulus histograms of the PBO nanocomposite films prepared in Examples 1-4 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0036] A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film comprises the following steps: (1) Preparation of PBO nanofiber dispersion: PBO fibers were added to mixed acid at a mass ratio of 1:(200-400) and stirred at 25°C-40°C for 2-3 days to obtain PBO nanofiber dispersion; (2) Preparation of MXene nanosheets modified with natural polyphenol compounds: natural polyphenol compounds and MXene nanosheets were ultrasonically dispersed in deionized water at a mass ratio of (1-5):1 to obtain a dispersion containing 4-8 mg / mL MXene nanosheets. A pH regulator was then added to the obtained dispersion until the pH of the system was 8-9. The mixture was stirred at 25-30 °C for 12-24 h, and then freeze-dried at a vacuum degree of 6.0-10.0 Pa and a temperature of -50-99 °C for 24-72 h to obtain MXene nanosheets modified with natural polyphenol compounds. (3) Preparation of PBO / MXene nanocomposite film: The mass ratio of MXene nanosheets modified by natural polyphenol compounds to PBO fibers is 1:(1~4). The nanosheets modified by natural polyphenol compounds and PBO nanofiber dispersions are taken separately, and then the nanosheets modified by natural polyphenol compounds are added to the PBO nanofiber dispersion. After stirring for 15~20 minutes to make it uniform, a mixed acid aqueous solution is added dropwise at a mass ratio of (285~315) to the PBO fibers in the PBO nanofiber dispersion to obtain a PBO / MXene nanocomposite acid sol; the sol is allowed to stand for 24 hours to obtain an acid gel, and then a solvent exchange is carried out in a methanesulfonic acid aqueous solution and water to obtain a PBO / MXene nanocomposite hydrogel; the sol is then calendered at 0.6~1.0 kPa and dried at 30℃~50℃ for 24~48 hours to obtain a PBO / MXene nanocomposite film.
[0037] Wherein, the mixed acid in step (1) is prepared by mixing methanesulfonic acid (MSA) and trifluoroacetic acid (TFA) in a mass ratio of 1:(1.0-1.5).
[0038] The natural polyphenol compound in step (2) is selected from any one of tannic acid, ellagic acid, epigallocatechin gallate, chlorogenic acid, catechin, and quercetin. The pH adjuster is selected from any one of ammonia water, sodium hydroxide, sodium carbonate, sodium bicarbonate, and tris(hydroxymethyl)aminomethane.
[0039] The mixed acid aqueous solution in step (3) is prepared by mixing methanesulfonic acid, ethyl acetate, and water in a mass ratio of 400:(115-130):(15-25). The mass ratio of methanesulfonic acid to water in the methanesulfonic acid aqueous solution is (0-4):1; the immersion time in the methanesulfonic acid aqueous solution is 12 hours; and the number of immersions in water is 6-13 times, each immersion lasting 1-2 hours.
[0040] The technical solutions of the present invention will be further described below with reference to specific embodiments. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. All technologies implemented based on the above content of the present invention are included in the scope of protection intended by the present invention.
[0041] The raw materials used in the following examples are described as follows: Ti3AlC2, PBO fiber, hydrochloric acid, lithium fluoride, ethyl acetate, methanesulfonic acid, trifluoroacetic acid, natural polyphenol compounds, and pH regulator are all commercially available products, wherein the mass fraction of hydrochloric acid is 37 wt%.
[0042] The in-plane thermal conductivity involved in the following examples was measured using a laser flash method, the limiting oxygen index was tested in accordance with ISO 4589-2, and the tensile strength was tested in accordance with GB / T 1040.3.
[0043] Ti3C2T was prepared by etching layering method. x Nanosheets: 1.6 g of LiF was added to 20 ml of 8 mol / L HCl solution and stirred until completely dissolved to prepare an etching solution; 1 g of Ti3AlC2 was added to the above etching solution and magnetically stirred at 30 ° C for 48 h to etch away the Al atoms in Ti3AlC2 to obtain Ti3C2T x The mixed acid solution was washed with deionized water and centrifuged until the supernatant PH> 6, and the supernatant was removed to obtain a multilayer Ti3C2T x Deionized water was added to the resulting precipitate, shaken and then centrifuged, the supernatant was collected and placed in a refrigerator for 3 hours; then freeze-dried at -99 ° C, 8Pa vacuum for 48 hours to obtain Ti3C2T x Nanosheet powder.
[0044] Example 1 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 25 °C for 3 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Tannic acid modified Ti3C2T x Preparation of nanosheets: 0.4 g tannic acid and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Tris(hydroxymethyl)aminomethane buffer was then added to adjust the pH of the system to 8.0. After stirring at 30 °C for 12 h, the mixture was freeze-dried at 6.0 Pa and -99 °C for 48 h to obtain tannic acid-modified Ti3C2T x nanosheets; (3) PBO / Ti3C2T x Preparation of nanocomposite film: 0.023g of tannic acid modified Ti3C2T x The nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 15 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T xThe nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 h for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 h each. It was then immersed in water for 1 h and the water was changed and immersed 12 times to completely remove the acid. x Nanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 0.6 kPa and dried at 40 °C for 24 h to prepare PBO / 40 wt% TA-Ti3C2T x Nanocomposite films.
[0045] Example 2 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 25 °C for 3 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Epigallocatechin gallate modified Ti3C2T x Preparation of nanosheets: 0.4 g epigallocatechin gallate and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Sodium bicarbonate was then added to adjust the pH of the system to 8.5. After stirring at 25 °C for 24 h, the mixture was freeze-dried at 10.0 Pa and -99 °C for 24 h to obtain Ti3C2T modified with epigallocatechin gallate. x nanosheets; (3) PBO / Ti3C2T x Preparation of nanocomposite film: Ti3C2T modified with 0.023g epigallocatechin gallate was firstly x The nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 15 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T x The nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 h for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 h each. It was then immersed in water for 2 h and the water was changed and immersed 8 times to completely remove the acid. PBO / Ti3C2T xNanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 0.6 kPa and dried at 40 °C for 24 h to prepare PBO / 40 wt% GA-Ti3C2T x Nanocomposite films.
[0046] Example 3 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 25 °C for 3 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Catechin-modified Ti3C2T x Preparation of nanosheets: 0.4 g catechin and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Then, sodium hydroxide was added to adjust the pH of the system to 9.0. After stirring at 30 °C for 12 h, the mixture was freeze-dried at 6.0 Pa and -99 °C for 72 h to obtain catechin-modified Ti3C2T x nanosheets; (3) PBO / Ti3C2T x Preparation of nanocomposite film: 0.023g catechin-modified Ti3C2T x The nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 20 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T x The nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 hours for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 hours each, and then immersed in water for 2 hours. The water was changed and immersed for 6 times to completely remove the acid, and the PBO / Ti3C2T x Nanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 0.6 kPa and dried at 40 °C for 24 h to prepare PBO / 40 wt% DOPA-Ti3C2T x Nanocomposite films.
[0047] Example 4 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 25 °C for 3 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Quercetin modified Ti3C2T x Preparation of nanosheets: 0.4 g quercetin and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Ammonia was then added to adjust the pH of the system to 9.0. After stirring at 30 °C for 12 h, the mixture was freeze-dried at 8.0 Pa and -99 °C for 48 h to obtain quercetin-modified Ti3C2T x nanosheets; (3) Preparation of PBO / MXene nanocomposite film: 0.023 g of quercetin-modified Ti3C2T x The nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 15 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T x The nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 hours for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 hours each. It was then immersed in water for 1 hour and the water was changed and immersed 12 times to completely remove the acid. In order to completely remove the acid, PBO / Ti3C2T x Nanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 0.6 kPa and dried at 40 °C for 24 h to prepare PBO / 40 wt% EGC-Ti3C2T x Nanocomposite films.
[0048] Example 5 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 25 °C for 3 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Tannic acid modified Ti3C2T xPreparation of nanosheets: 0.4 g tannic acid and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Tris(hydroxymethyl)aminomethane buffer was then added to adjust the pH of the system to 8.0. After stirring at 30 °C for 12 h, the mixture was freeze-dried at 10.0 Pa and -99 °C for 24 h to obtain tannic acid-modified Ti3C2T x nanosheets; (3) PBO / Ti3C2T x Preparation of nanocomposite film: 0.009g of tannic acid modified Ti3C2T x The nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 15 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T x The nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 h for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 h each. It was then immersed in water for 1 h and the water was changed and immersed 12 times to completely remove the acid. x Nanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 0.8 kPa and dried at 30 °C for 48 h to prepare PBO / 20 wt% TA-Ti3C2T x Nanocomposite films.
[0049] Example 6 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 40 °C for 2 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Tannic acid modified Ti3C2T x Preparation of nanosheets: 0.4 g tannic acid and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Tris(hydroxymethyl)aminomethane buffer was then added to adjust the pH of the system to 8.0. After stirring at 30 °C for 12 h, the mixture was freeze-dried at 8.0 Pa and -99 °C for 24 h to obtain tannic acid-modified Ti3C2Tx nanosheets; (3) PBO / Ti3C2T x Preparation of nanocomposite film: 0.015g of tannic acid modified Ti3C2T x The nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 15 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T x The nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 h for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 h each. It was then immersed in water for 1 h and the water was changed and immersed 12 times to completely remove the acid. x Nanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 0.8 kPa and dried at 40 °C for 24 h to prepare PBO / 30 wt% TA-Ti3C2T x Nanocomposite films.
[0050] Example 7 A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film: (1) Preparation of PBO nanofiber dispersion: 0.35 g of PBO fibers were added to a mixed acid solution consisting of 50 g of MSA and 50 g of TFA and stirred at 40 °C for 2 days to obtain a 0.35 wt% PBO nanofiber dispersion. (2) Tannic acid modified Ti3C2T x Preparation of nanosheets: 0.4 g tannic acid and 0.4 g Ti3C2T x The nanosheets were ultrasonically dispersed in 100 mL of deionized water to obtain a mixed dispersion. Tris(hydroxymethyl)aminomethane buffer was then added to adjust the pH of the system to 8.0. After stirring at 30 °C for 12 h, the mixture was freeze-dried at 8.0 Pa and -99 °C for 24 h to obtain tannic acid-modified Ti3C2T x nanosheets; (3) PBO / Ti3C2T x Preparation of nanocomposite film: 0.035g of tannic acid modified Ti3C2T xThe nanosheets were ultrasonically dispersed in 10.0 g of the prepared 0.35 wt% PBO nanofiber dispersion and mechanically stirred for 15 min to obtain PBO / Ti3C2T x The mixed solution was then added dropwise with a mixed solvent consisting of 7.76 g MSA, 2.23 g EA, and 0.29 g H2O to obtain PBO / Ti3C2T x Nanocomposite acid sol; PBO / Ti3C2T x The nanocomposite acid sol was poured into a culture dish and allowed to stand for 24 h for gelation and aging. The obtained acid gel was then placed in a mixture of MSA and H2O in a mass ratio of 4:1 and 7:3, respectively, and immersed for 12 h each. It was then immersed in water for 1 h and the water was changed and immersed 12 times to completely remove the acid. x Nanocomposite hydrogel; Subsequently, PBO / Ti3C2T x The nanocomposite hydrogel was calendered under a pressure of 1.0 kPa and dried at 40 °C for 24 h to prepare PBO / 50 wt% TA-Ti3C2T x Nanocomposite films.
[0051] Comparative Example 1 Compared with Example 1, the difference is that step (2) of tannic acid-modified Ti3C2T x Preparation of nanosheets and step (3) of tannic acid modified Ti3C2T x The addition of nanosheets and other steps were the same as in Example 1 to obtain pure PBO nanofilm.
[0052] Comparative Example 2 Compared with Example 1, the difference is that step (2) tannic acid modified Ti3C2T x Preparation of nanosheets: 0.023 g of unmodified Ti3C2T x Nanosheets, other steps are the same as in Example 1, to obtain PBO / 40wt%Ti3C2T x Nanocomposite films.
[0053] Comparative Example 3 Compared with Example 1, the difference is that step (2) tannic acid modified Ti3C2T x In the preparation of nanosheets, 0.023 g of tannic acid was added in step (3), and the other steps were the same as those in Example 1 to obtain a PBO / 40 wt% TA nanocomposite film.
[0054] Performance Testing Figure 1 PBO / 40wt%TA-Ti3C2T prepared in Example 1 xOptical photograph of the nanocomposite film. As can be seen from the figure, the prepared nanocomposite film can be continuously wound and exhibits good flexibility.
[0055] PBO / 40wt%TA-Ti3C2T prepared in Example 1 x The cross-sectional SEM images of the nanocomposite film are shown in Figure 2. Figure 2 As shown in the figure, it can be observed that the cross-section of the nanocomposite film presents a dense layered structure similar to the oriented structure of the nacre layer of shells, indicating that a strong interfacial force is formed between the PBO nanofibers and the tannic acid-modified MXene.
[0056] The PBO films prepared in Example 1 and Comparative Examples 1-2 are used as the heat dissipation substrate of the ceramic heating plate, and the infrared thermal imaging comparison diagrams are shown in FIG. Figure 3 From the comparison of the figures, it can be found that after the nanocomposite film prepared in Example 1 is heated to 234.3°C for 60s and then cooled for 30s, its surface temperature quickly drops to 136.7°C, indicating that it has a higher thermal conductivity and better heat dissipation effect.
[0057] PBO / 40wt%TA-Ti3C2T prepared in Example 1 x The tensile cross-section SEM image of the nanocomposite film is shown in Figure 2. Figure 4 As shown in the figure, the crack propagation process of the nanocomposite film is accompanied by the slip and pullout of MXene nanosheets, as well as the elongation and fracture of PBO nanofibers, proving that the synergistic effect of the nanosheet and nanofiber structure gives the nanocomposite film excellent mechanical properties.
[0058] The stress-strain curves and strength-modulus histograms of the PBO films prepared in Examples 1-4 and Comparative Examples 1-3 are shown in FIG. Figure 5 As shown. Figure 5 By comparison, it can be found that the PBO films prepared in Examples 1-4 have excellent tensile strength, elongation at break and Young's modulus, showing better mechanical properties.
[0059] The thermal conductivity, limiting oxygen index and tensile strength of the PBO films prepared in Examples 1-7 and Comparative Examples 1-3 were tested. The specific test results are shown in Table 1.
[0060] Table 1 Performance test results of the films obtained in Examples 1-7 and Comparative Examples 1-3
[0061] From the data in Table 1, it can be seen that the thermal conductivity of the pure PBO film prepared in Comparative Example 1 is 25.2 W m -1 K -1 , the limiting oxygen index is 53.5%. Comparative Example 2 adds Ti3C2T xPBO / Ti3C2T prepared by nanosheets x The thermal conductivity, limiting oxygen index and mechanical properties of the nanocomposite film are all improved; and the mechanical properties of the PBO / TA nanocomposite film prepared by adding tannic acid in comparative example 3 are greatly improved, which is due to the fact that tannic acid can enhance the interaction between PBO nanofibers.
[0062] Compared with the comparative example, the PBO nanocomposite films modified with natural polyphenol compounds in Examples 1-4 showed better thermal conductivity, flame retardancy and mechanical properties, and their thermal conductivity was greater than 37 W m -1 K -1 , a tensile strength greater than 240 MPa, and a limiting oxygen index greater than 54%. The PBO nanocomposite film prepared with tannic acid-modified MXene exhibited the best overall performance. This is due to the strong π-π interactions and hydrogen-bonding crosslinking between the natural polyphenol-modified MXene and the PBO nanofiber matrix. These interactions not only improve dispersibility and enhance interfacial interactions, but also provide additional thermal bridges, effectively reducing interfacial thermal resistance and further enhancing in-plane thermal conductivity. Furthermore, the introduction of the natural polyphenol enhances its interaction with the PBO nanofibers through strong hydrogen bonds, forming a fine "brick-and-mud" oriented structure that mimics the nacreous shell layer, enhancing mechanical properties. Furthermore, the natural polyphenol's excellent char-forming properties and free radical-scavenging abilities synergize with the MXene and PBO nanofibers during combustion, significantly improving flame retardancy.
[0063] At the same time, compared with Examples 5-7, the PBO / 40wt%TA-Ti3C2T prepared in Example 1 x The nanocomposite film has the best comprehensive performance.
[0064] It should be noted that although the above embodiments have been described herein, this does not limit the scope of patent protection of the present invention. Therefore, based on the innovative concept of the present invention, changes and modifications to the embodiments described herein, or equivalent structural or equivalent process transformations made using the contents of the present invention specification, and direct or indirect application of the above technical solutions to other related technical fields are all included in the scope of patent protection of the present invention.
Claims
1. A method for preparing a highly thermally conductive flame-retardant PBO nanocomposite film, characterized in that: The following steps are involved: (1) Preparation of PBO nanofiber dispersion: PBO fibers were added to mixed acid and stirred to obtain PBO nanofiber dispersion; (2) Preparation of MXene nanosheets modified with natural polyphenol compounds: natural polyphenol compounds and MXene nanosheets are ultrasonically dispersed in deionized water, and then a pH regulator is added to the dispersion until the system becomes weakly alkaline. After stirring, the mixture is freeze-dried to obtain MXene nanosheets modified with natural polyphenol compounds; (3) Preparation of PBO / MXene nanocomposite film: MXene nanosheets modified with natural polyphenol compounds are added to the PBO nanofiber dispersion, stirred evenly, and then a mixed acid aqueous solution is added dropwise to obtain a PBO / MXene nanocomposite acid sol; after standing, the sol is subjected to solvent exchange to obtain a PBO / MXene nanocomposite hydrogel; and then the sol is calendered and dried to obtain a PBO / MXene nanocomposite film.
2. The preparation method according to claim 1, characterized in that The mixed acid in step (1) is prepared by mixing methanesulfonic acid and trifluoroacetic acid in a mass ratio of 1:(1.0-1.5); the mass ratio of the PBO fiber to the mixed acid is 1:(200-400); the stirring temperature is 25°C-40°C, and the stirring time is 2-3 days.
3. The preparation method according to claim 1, characterized in that The natural polyphenol compound in step (2) is selected from any one of tannic acid, ellagic acid, epigallocatechin gallate, chlorogenic acid, catechin, and quercetin; the mass ratio of the natural polyphenol compound to the MXene nanosheets is (1-5):1; and the concentration of the MXene nanosheets in the obtained dispersion is 4-8 mg / mL.
4. The preparation method according to claim 1, characterized in that The pH regulator in step (2) is selected from any one of ammonia water, sodium hydroxide, sodium carbonate, sodium bicarbonate, and tris(hydroxymethyl)aminomethane, and the pH of the system is adjusted to 8-9.
5. The preparation method according to claim 1, characterized in that The stirring temperature in step (2) is 25°C~30°C, and the time is 12~24h; the vacuum degree of the freeze-drying is 6.0~10.0Pa, the temperature is -50°C~-99°C, and the time is 24h~72h.
6. The preparation method according to claim 1, characterized in that The mass ratio of the natural polyphenol compound modified nanosheets used in step (3) to the PBO fibers in the PBO nanofiber dispersion is 1:(1-4); the mixed acid aqueous solution is prepared by mixing methanesulfonic acid, ethyl acetate and water in a mass ratio of 400:(115-130):(15-25), and the mass ratio of the mixed acid aqueous solution to the PBO fibers in the PBO nanofiber dispersion is (285-315):
1.
7. The preparation method according to claim 1, characterized in that The standing time in step (3) is 24 hours; the solvent exchange is first soaking in a methanesulfonic acid aqueous solution and then soaking in water; the mass ratio of methanesulfonic acid to water in the methanesulfonic acid aqueous solution is (0-4):1; the soaking time in the methanesulfonic acid aqueous solution is 12 hours; the number of soaking in water is 6-13 times, each soaking is 1-2 hours.
8. The preparation method according to claim 1, characterized in that The calendering pressure in step (3) is 0.6~1.0kPa; the drying temperature is 30℃~50℃, and the drying time is 24~48h.
9. A high thermal conductivity flame retardant PBO nanocomposite film, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. The high thermal conductivity and flame retardant PBO nanocomposite film according to claim 9, characterized in that: Its thermal conductivity is greater than 37 W·m -1 K -1 , tensile strength greater than 240 MPa, and limiting oxygen index greater than 54%.
Citation Information
Patent Citations
MXene-edge graphene oxide heterojunction / PBO fiber multifunctional heat-conducting composite film and preparation method thereof
CN119823426A
Cited By
A method for preparing a pbo nanofiber film having an in-plane orientation
CN122790260A